Study on influence of lateral liquid feeding into crystallizer on solidification process of copper billets. (October 2018) - Han, Yi; Xiao, Yao; Zhang, Ao-Yin; Liu, Feng; Yu, En-Lin; Gao, Ying
Highlights: Casting liquid in a crystallizer with lateral opening exhibits spiral swirling flow. The grains of casting billet in a crystallizer with lateral opening are finer. When the lateral tilt angle is 10° the density of grains is the largest. Abstract: The first process in the production, namely, horizontal continuous casting process, directly influences the performances of finished copper tubes. Numerical calculation and comparative analysis were conducted for the flow field and microstructural field of the flow and solidification of casting liquid in two kinds of crystallizers for horizontal continuous casting. It was found that the internal factors influencing the internal heat exchange effect of crystallizer and the microstructural uniformity of casting billets are swirl effect, and turbulence intensity. The structural parameters of liquid inlet of a crystallizer with lateral opening, i.e., the forward tilt angle and lateral tilt angle of liquid inlet, were analyzed from the source, and the reasonable parameter values of liquid inlet for improving the quality of casting billets were finally obtained with the mean value of maximum spin speed, the turbulence intensity, and the microstructural grain size of casting billet as evaluation criteria. The accuracy of the numerical calculation was visually verified through metallographic experimental analysis. This study provides measurable reference theoretical basis for production of inner grooved copper tube with efficient heat exchange.